2019
DOI: 10.30964/auebfd.539374
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmenlik Uygulamasının Süre Açısından İncelenmesi ve Bir Çözüm Önerisi

Abstract: This study aims to reveal the views of prospective teachers, teachers, school managers and teaching staffs about the duration of the teaching practicum in teacher training programs. Later, this study aims to make comparisons between Turkey, Finland, Singapore and Germany, and to propose an alternative application for Turkey. In this study, a qualitative research method was preferred. Study group of this study consist of 28 persons. Eight students from the education faculty, eight teachers, four school managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Participants who offered suggestions for the solution of the current problems mentioned especially that the lecturers teaching the teaching practice course should be selected from the field and their internship duration should be increased. In his study, Tosun (2019) concluded that the internship period was insufficient. Similarly, Aslan and Sağlam (2018) stated that pre-service teachers found the class hours for teaching practice insufficient, and because of the inadequacy of the internship period, the pre-service teachers were unable to adequately familiarize with and experience the practices in the school.…”
Section: Discussionmentioning
confidence: 99%
“…Participants who offered suggestions for the solution of the current problems mentioned especially that the lecturers teaching the teaching practice course should be selected from the field and their internship duration should be increased. In his study, Tosun (2019) concluded that the internship period was insufficient. Similarly, Aslan and Sağlam (2018) stated that pre-service teachers found the class hours for teaching practice insufficient, and because of the inadequacy of the internship period, the pre-service teachers were unable to adequately familiarize with and experience the practices in the school.…”
Section: Discussionmentioning
confidence: 99%
“…Ancak literatür incelendiğinde yapılan çalışmalar Türkiye'deki öğretmen adaylarının özellikle staj eğitimi dönemlerinde yaşadığı birçok problemi gözler önüne sermektedir. Bu problemlerden bazıları öğretmen adaylarının haftada bir gün gibi çok az süreyle staja gitmeleri, sınıf yönetiminde zorluk yaşamaları, staja gittikleri okuldaki öğrencileri yeterince tanıyamamaları ve öğrencilerle iletişim kurmada sıkıntı yaşamaları şeklinde özetlenebilir (Tosun, 2019).…”
Section: Introductionunclassified
“…It is applied in schools affiliated to the Ministry of National Education. Turkey, in the 2018-2019 academic years, began to apply a new undergraduate teaching program last year in which a teaching practice of a total of 24 days, including 12 days for each semester is carried out [5]. The practicum gives prospective teachers the opportunity to recognize and apply the profession [6].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Altan, et al [13] put forward that the practicum period assigned to re-service teachers is limited to attain the needed skills. Tosun [5] also examined the teaching practicum with respect to the time period assigned to it and found out that the time allocated to practicum practices in Turkey is highly limited compared to the practices in Finland and Germany. Özer and Alkan [14] also found out that in such countries as the UK, Portugal, Spain, Italy, and Belgium, the practicum is carried out every school year.…”
Section: Introductionmentioning
confidence: 99%